Optimizing Mathematics Teacher Candidates' Complex Problem-Solving Skills: A Comprehensive Analysis of The Effectiveness of The Problem-Based Learning Model - Pamungkas, Megita Dwi; Rahmawati, Fadhilah; Kusuma, Jaka Wijaya; Kontoko, Kintoko; Purnomo, Eko Andy (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
Complex problem solving" ability as a 21st-century skill students need to solve dynamically changing problems. Students of prospective mathematics teachers are said to master complex problem situations if possible, therefore a learning model is needed that can improve the ability to solve complex problems for prospective mathematics teacher students, one of which uses problem-based learning (PBL). The purpose of this study is to get an overview of improving the ability to solve complex problems of prospective mathematics teacher students after learning with the Problem Based Learning (PBL) model at Tidar University with the subject of second semester students of the Mathematics Education Study Program. This research will be conducted using a quasi-experimental method, with a nonequivalent control group pretest-posttest research design. Research instruments in the form of complex problem solving tests, observation sheets on learning implementation, and interview guidelines. The results showed that PBL is more effective than conventional learning on complex problem-solving skills. In addition, the results also show that problem-based learning (PBL) is effective in improving the complex problem-solving ability of prospective mathematics teacher students. The results of the increase test with N-Gain obtained an average of 0.43 which belongs to the category of moderate increase